Learners' challenges in reading and writing in english first additional language in the Intermediate Phase in Mankweng Circuit - Sebetoa, Phillimon More (My University, 2016)
Learners in rural areas are disadvantaged in terms of exposure to English First Additional Language (EFAL).They require more basic attention in reading and writing skills. For this reason, the study analyses why Intermediate Phase learners in schools in rural areas are struggling to read and write in EFAL. In view of this, Darara (2012:4) argues that reading and writing is not an educational hurdle affecting only learners at Intermediate Phase in schools. The purpose of this study is to bring to light learners’ challenges in reading and writing in EFAL at Intermediate Phase. The study thus employs how to eliminate learners’ reading and writing challenges emanating at this phase. The method used in this study is qualitative and it is used in order for teachers to bring out their experiences on EFAL teaching. Data collection was done through structured interviews and non-participant observation. Nine teachers were sampled from three primary schools in the Mankweng Circuit. Each school forwarded three teachers, this means one from each intermediate grades. The research results from both interviews and observations are jointly presented in order to avoid repetitions. The researcher presents profiles of schools and teachers together with the way reading and writing are conducted in schools. The study, in its presentation, highlights the way teachers are moved around the province through the government programme Rationalisation and Redeployment. Amongst the findings revealed by the study, most of the teachers do not take English as their major subject in their teaching career. This is one reason why reading and writing at Intermediate Phase in rural schools is almost unachievable. The study recommends that EFAL teachers conduct workshops and training with fellow teachers in ex-model C and private schools to learn from each other in order to overcome challenges emanating from the two skills.
Thesis (M. Ed.(Language Education)) -- University of Limpopo, 2016
Keywords: English First Additional Language; Intermediate phase learners; Reading; Writing; English language -- Study and teaching (Primary) -- South Africa -- Limpopo; Reading(Primary) -- South Africa -- Limpopo; English language -- Writing